2010
DOI: 10.1590/s0100-29452010005000002
|View full text |Cite
|
Sign up to set email alerts
|

Enxertia da cajazeira

Abstract: RESUMO-A necessidade de técnicas de propagação assexuada recomendadas para a produção comercial de mudas limita a expansão comercial da cajazeira. Portanto, foi instalado um experimento na Empresa de Pesquisa Agropecuária da Paraíba -EMEPA, com o objetivo de avaliar o melhor método de enxertia para a cajazeira. Adotou-se o delineamento experimental em blocos ao acaso, com quatro repetições, em esquema de parcelas subdivididas no tempo, estando nas parcelas os métodos de enxertia (garfagem em fenda cheia, inglê… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 2 publications
0
3
0
2
Order By: Relevance
“…LSL as a function of the cultivars did not differ statistically from each other for the cultivars African Pride (15.3 cm) and Thompson (13.7 cm), showing better results than the cultivar Gefner (1.2 cm). Souza et al (2010) found contrary results when working with different grafting methods on yellow mombin (Spondias mombin). The authors observed the longest bud length for the splice graft method and concluded that the cleft graft and side graft methods did not differ from each other.…”
Section: Resultsmentioning
confidence: 97%
“…LSL as a function of the cultivars did not differ statistically from each other for the cultivars African Pride (15.3 cm) and Thompson (13.7 cm), showing better results than the cultivar Gefner (1.2 cm). Souza et al (2010) found contrary results when working with different grafting methods on yellow mombin (Spondias mombin). The authors observed the longest bud length for the splice graft method and concluded that the cleft graft and side graft methods did not differ from each other.…”
Section: Resultsmentioning
confidence: 97%
“…Almeida (2009), estudando os métodos de enxertia de atemoia em espécies de Rollinia, verificou que os portaenxertos exercem influência na escolha do método de enxertia, observando que o método fenda lateral conferiu o maior comprimento de ramo sobre o porta-enxerto araticum-de-terra-fria e, em biriba, o método de enxertia que induziu maior comprimento de ramo foi a enxertia à inglesa simples. Souza et al (2010) verificaram diferença significativa entre as modalidades de enxertia, quanto ao comprimento dos ramos; com a enxertia à inglesa, simples, apresentando comprimento maior que o dos métodos de garfagem em fenda cheia e garfagem em fenda lateral, que não diferiram entre si.…”
Section: Fonte De Variaçãounclassified
“…2016ro de estacas brotadas e de sobrevivência dos enxertos, contrariando os resultados encontrados neste estudo Souza et al (2010). não encontraram diferença significativa para o número de ramos entre os métodos de enxertia em cajazeira.…”
unclassified
“…The extract was left 24 hours in the dark at 4 °C, (SOUZA et al, 2006;2010). In Northeastern Brazil, the demand for yellow mombin pulp is greater than other commercialized fruit pulps (FRAIFE FILHO;LEITE;RAMOS, 2010); however, its industrialization is totally dependent on seasonal variation in fruit taking into account the extractive exploitation of the yellow mombin tree and the elevated fruit losses due to poor harvesting practices, postharvest handling, and transportation (MOURA et al, 2004;2009;SOARES et al, 2006).…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…Therefore, the increased demand for yellow mombin fruits has attracted interest to the cultivation of this species, which is still considered in the process of domestication with little information about the establishment of commercial orchards (SOUZA et al, 2006). Its inclusion as a fruit species in the modern agronomic models requires, however, the identification of propagated materials whose genotypes that in addition to having high productive capacity (AZEVEDO; MENDES; FIGUEIREDO, 2004;CASSIMIRO;MACÊDO;MENINO, 2009;SOUZA et al, 2010) can produce fruits with superior functional quality (SOARES et al, 2006;DANTAS JÚNIOR, 2008).…”
Section: Bioactive Compoundsmentioning
confidence: 99%